Restorative procedures in posterior teeth placed during a graduation course clinic: Quantitative evaluation about amalgam versus composite resin - Ana Del Carmen Armas-Vega; Thaís Thomé; Celso Rosin; Narciso Garone Netto; Maria Aparecida Alves de Cerqueira Luz (Universidade Estadual de Campinas, 2016)
A demand increase for aesthetic procedures in Dentistry has been observed due to the crescent interests of patients and the evolution of aesthetic restorative materials. The dental files of patients assisted at the clinic of the graduation course of restorative dentistry, School of Dentistry, University of São Paulo, were analyzed during the period from 1998 to 2003, with the purpose of accomplishing an evaluation of the assisted population as well as a longitudinal comparative study of the percentage of class I and class II restorations with amalgam or composite resin in posterior teeth placed by dental students. In the analyzed period, the amalgam was used in 28.5% of the class I and 27.5% of the class II whereas the composite resin was used in 32.1% of the class I and 11.9% of the class II restorations. Although the class I posterior composite resin restorations had been made in a higher proportion and an increase of these procedures was observed, the class II amalgam restorations were predominant along the analyzed period. The prevalent group was between 31 and 40 years old and female gender. Although there were prevalence of class II amalgam restorations placed, there was an increase of the resin composite restorations in posterior teeth when compared with amalgam restorations, mainly in class I cavity restorations, probably due to its conservative characteristics.